anonymous
  • anonymous
f(x)=-15x+1 g(x)=-15x^2-20x-5 find (gof)(-3)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
woah that looks confuzing, okay: f(x)=15x+1 g(x)=-15x\[^{2}\]-20x-5 find (g o f)(3)
anonymous
  • anonymous
*-3, sorry
Hero
  • Hero
f(x)=-15x+1 g(x)=-15x^2-20x-5 f(-3) = -15(-3) + 1 = 45 + 1 = 46 (g o f)(-3) = g(f(-3)) = g(46) g(46) = -15(46)^2 - 20(46) - 5 = -31740 - 920 - 5 = -32665

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

Hero
  • Hero
That should be the correct answer
anonymous
  • anonymous
dude you're awesome. i remember that now. so you solve f(-3) and then put it into g ?
Hero
  • Hero
The general formula is: (f o g)(x) = f(g(x)) But in this case we have: (g o f)(-x), so we write: (g o f)(-x) = g(f(-x)), then solve.
anonymous
  • anonymous
sweethanks !!! could you help me with one more problem?
Hero
  • Hero
Post it

Looking for something else?

Not the answer you are looking for? Search for more explanations.